High light-induced changes in whole-cell proteomic profile and its correlation with the organization of thylakoid super-complex in cyclic electron transport mutants of Chlamydomonas reinhardtii - Yadav, Ranay Mohan; Marriboina, Sureshbabu; Zamal, Mohammad Yusuf; Pandey, Jayendra; Subramanyam, Rajagopal (Frontiers in Plant Science, 2023)
Light and nutrients are essential components of photosynthesis. Activating the signalling cascades are critical in starting adaptive processes in response to high light. In this study, we have used wild-type (WT), Proton Gradient Regulation (PGR) Like 1 (PGRL1) and PGR5 mutants to elucidate the actual role in regulation and assembly of photosynthetic pigment-protein complexes under high light. Here we have correlated the biophysical, biochemical, and proteomic approaches to understand the targeted proteins and the organization of thylakoid pigment-protein complexes in the photoacclimation. The proteomic analysis showed 320 proteins were significantly affected under high light than the control and are mainly involved in the photosynthetic electron transport chain, protein synthesis, metabolic process, glycolysis, and proteins involved in cytoskeleton assembly. Additionally, we observed that the Cyt b6 expression is increased in the pgr5 mutant to regulate pmf and ATPase across the thylakoid membrane. The increased Cyt b6 function in pgr5 could be due to the compromised function of chloroplast (cp) ATP synthase subunits for energy generation and photoprotection under high light. Moreover, our proteome data shows that the photosystem subunit II (PSBS) protein isoforms (PSBS1 and PSBS2) expressed more than Light-Harvesting Complex Stress-Related (LHCSR) protein in pgr5 compared to WT and pgrl1 under high light. In addition, we immunoblotted the photosystems (PS) II and PSI core and associated light-harvesting complexes proteins to compare with the total cell proteome. The PSII proteins D1 and D2 accumulated more in pgrl1 and pgr5 than WT under high light. In high light, CP43 and CP47 showed a reduced amount in pgr5 under high light due to changes in chlorophyll and carotenoid content around the PSII protein, which coordinates as cofactors for efficient energy transfer from the light-harvesting antenna to the photosystem core. BN-PAGE and circular dichroism studies indicate changes in macromolecular assembly and thylakoid super complexes destacking in pgrl1 and pgr5 due to changes in the pigment-protein complexes under high light. Based on this study, we emphasize that this is an excellent aid in understanding the role of CET mutants in thylakoid proteins abundances and super-complex organization under high light.